1990
DOI: 10.1103/physrevlett.65.988
|View full text |Cite
|
Sign up to set email alerts
|

Argon-photoion–Auger-electron coincidence measurements followingK-shell excitation by synchrotron radiation

Abstract: Argon photoion spectra have been obtained for the first time in coincidence with K-LL and K-LM Auger electrons, as a function of photon energy. The simplified charge distributions which result exhibit a much more pronounced photon-energy dependence than do the more complicated noncoincident spectra. In the near-AT-threshold region, Rydberg shakeoff of np levels, populated by resonant excitation of K electrons, occurs with significant probability, as do double-Auger processes and recapture of the K photoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…The details of the FCSD of Argon ions with the initial 1 s hole is summarized in Table 1. Excellent agreement between the theoretical RACS result and the available experimental data [6][7][8] is obtained, as shown in Fig. 1.…”
Section: Fcsd With the 1 S Hole In Arsupporting
confidence: 68%
See 1 more Smart Citation
“…The details of the FCSD of Argon ions with the initial 1 s hole is summarized in Table 1. Excellent agreement between the theoretical RACS result and the available experimental data [6][7][8] is obtained, as shown in Fig. 1.…”
Section: Fcsd With the 1 S Hole In Arsupporting
confidence: 68%
“…Some discrepancy was found in the case of the 2p hole, where the method seems to overestimate the SKOF contribution. The model is also capable of predicting in detail the X-ray and Auger spectra produced in the cascade decay of the initial hole [8], as well as that resulting from the primary SKOF. The discrepancy in the FCSD found in the earlier study with the R A C model is shown to be due to the shake-off effect in the initial stage of the hole production.…”
Section: Discussionmentioning
confidence: 99%
“…The charge state and photoion spectra were studied for Ne [3,49], Ar [4,11,12,[50][51][52][53], Kr [5,6,33,[53][54][55][56], Xe [6,9,16,34,35,46,[57][58][59][60], and for all of them [61][62][63]. Also such spectra were investigated for lanthanides [7-9, 15, 32, 64-66], Mg [50,67], Al, Si, S, Ca, Fe [50], Cu [18], Sr [68], Ba [69], Au [70], Re [71], and Ta [71].…”
Section: Introductionmentioning
confidence: 99%
“…A few examples are photon-ion interactions, in which either the ion beam after the collision 2], or electrons emitted are detected; these ions can be highly charged. Other examples are coincidence experiments [3], where low collection efficiencies require intense photonbeams;experiments withactinide targets, wherematerial iseither scarce orhighlyradioactive; and laser-excited targets [4]. Many otherapplications inatomicphysics have been considered [5].…”
Section: Atomic Physics and Highly Charged Ionsmentioning
confidence: 99%